Outage Probability of Full-Duplex MIMO Relay Networks with Co-channel Interference over Rayleigh Fading Channels - Toka, Mesut; Kucur, Oğuz (IEEE, 2016)
In this work, the outage probability of dual-hop full-duplex amplify-and-forward MIMO relay network is examined in the presence of co-channel interference at the relay over Rayleigh fading channels. The source and destination are equipped with multiple antennas and the relay is equipped with single receive and single transmit antennas. The effects of Rayleigh faded multiple co-channel interferences and self-interference between transmit/receive antennas of the relay are considered. In this relay network, transmit antenna selection at the source and maximal-ratio combining technique at the destination are employed. The outage probability of the relay network is examined via Monte Carlo simulations.
24th Signal Processing and Communication Application Conference (SIU) -- MAY 16-19, 2016 -- Zonguldak, TURKEY
Keywords: Dual-hop relays; Full-duplex relay; Co-channel interference; Transmit antenna selection; Maximal-ratio combining